Endothelial-Ercc1 DNA repair deficiency provokes blood-brain barrier dysfunction - Cathrin E. Hansen; Davide Vacondio; Lennart van der Molen; Annika A. Jüttner; Wing Ka Fung; Manon Karsten; Bert van het Hof; Ruud D. Fontijn; Gijs Kooij; Maarten E. Witte; Anton J. M. Roks; Helga E. de Vries; et al. (Cell Death and Disease)
Abstract Aging of the brain vasculature plays a key role in the development of neurovascular and neurodegenerative diseases, thereby contributing to cognitive impairment. Among other factors, DNA damage strongly promotes cellular aging, however, the role of genomic instability in brain endothelial cells (EC) and its potential effect on brain homeostasis is still largely unclear. We here investigated how endothelial aging impacts blood-brain barrier (BBB) function by using excision repair cross complementation group 1 (ERCC1)-deficient human brain ECs and an EC-specific Ercc1 knock out (EC-KO) mouse model. In vitro, ERCC1-deficient brain ECs displayed increased senescence-associated secretory phenotype expression, reduced BBB integrity, and higher sprouting capacities due to an underlying dysregulation of the Dll4-Notch pathway. In line, EC-KO mice showed more P21+ cells, augmented expression of angiogenic markers, and a concomitant increase in the number of brain ECs and pericytes. Moreover, EC-KO mice displayed BBB leakage and enhanced cell adhesion molecule expression accompanied by peripheral immune cell infiltration into the brain. These findings were confined to the white matter, suggesting a regional susceptibility. Collectively, our results underline the role of endothelial aging as a driver of impaired BBB function, endothelial sprouting, and increased immune cell migration into the brain, thereby contributing to impaired brain homeostasis as observed during the aging process.